Telaprocera (Araneae: Araneidae), a new genus of Australian orb-web spiders with highly elongated webs - Harmer, Aaron M. T.; Framenau, Volker W. (Zootaxa, 2008)
A new genus of orb-web spider (Araneidae Simon), Telaprocera gen. nov., including two new species, T. maudae sp. nov. (type species) and T. joanae sp. nov., are described. Telaprocera gen. nov. differs from all other araneid genera by the presence of a dorsal keel on the male cymbium. The known range of Telaprocera maudae sp. nov. is limited to the east coast of Australia, from far northern Queensland to central New South Wales. The spiders are found in closed canopy rainforest and adults can be found year round. Telaprocera joanae sp. nov. has been found from central coastal Queensland to far eastern Victoria. They occur in similar habitats, with similar phenology, as T. maudae sp. nov. Both species build highly elongated orb-webs known as ladder-webs. A variety of phylogenetic analyses based on an updated morphological data matrix for orb-web spiders did not provide a conclusive placement of Telaprocera gen. nov. within the Araneidae. Equally weighted analysis placed the genus as sister to Kaira O. P.-Cambridge and Metepeira F. O. P.Cambridge combined. Strong downweighting of homoplasious characters placed the genus as sister taxon to the traditional Argiopinae Simon. The uncertain phylogenetic position of Telaprocera gen. nov. may reflect the insufficient knowledge of the morphology of Australian taxa—taxa that may possess characters previously not considered in phylogenetic analyses of the Araneidae.